Durability of externally strengthened concrete prisms with CFRP laminates and galvanized steel mesh attached with epoxy adhesives and mortar - Hawileh, Rami (2024)
The long-term bond degradation and strength retention of flexural bond prisms strengthened with carbon fiber-reinforced polymer (CFRP) composite and galvanized steel mesh (GSM) systems, bonded to concrete using epoxy adhesives and cement-based mortar under aggressive conditioning regimes are compared in this paper. Notched prisms strengthened using low-cord density steel mesh (LSM) with epoxy (SME-strengthened) and cement mortar (SMM-strengthened), and CFRP-epoxy systems were weathered under saline water and direct sunlight for a period of 28 and 540 days. The results of the study were analyzed based on experimentally obtained ultimate load (Pu) values and empirically calculated average bond shear stress (τavg) and prism strength retention (Rp) values. The bond strength degraded by 39 and 34 % in CFRP strengthened, 2.9 and 33 % in SME strengthened, and 2.8 and 10.8 % in SMM-strengthened specimens following the 540-day exposure to saline water and direct sunlight, respectively. The average prism retention ratio was calculated to be 0.61 and 0.66 for CFRP-strengthened, 0.97 and 0.67 for SME-strengthened, and 0.97 and 0.89 for SMM-strengthened specimens after 540 days of saline water and direct sunlight exposure. Flexural prism environment strength reduction factors (CE) were proposed as 0.60, 0.95, and 0.95 for CFRP, SME, and SMM-strengthened specimens under saline water exposures and 0.65, 0.65, and 0.85 for CFRP, SME, and SMM strengthened specimens under direct sunlight exposures. Saline water exposure was observed to be most critical to all strengthening systems. Although CFRP-strengthened specimens showed minimum degradation in load-carrying capacity under both conditioning regimes, they showed maximum bond strength reduction in contrast to SMM-strengthened specimens. It was observed that the choice of bonding agent significantly influenced the extent of bond strength degradation under extreme exposure regimes, like those that prevail in the UAE and the Persian Gulf.